Advising patients seeking stem cell interventions for multiple sclerosis. Issue 6 (30th May 2018) - von Wunster, Beatrice; Bailey, Steven; Wilkins, Alastair; Marks, David I; Scolding, Neil J; Rice, Claire M
Abstract : Given the intuitive potential of stem cell therapy and limitations of current treatment options for progressive multiple sclerosis (MS), it is not surprising that patients consider undertaking significant clinical and financial risks to access stem cell transplantation. However, while increasing evidence supports autologous haematopoietic stem cell transplantation (AHSCT) in aggressive relapsing–remitting MS, interventions employing haematopoietic or other stem cells should otherwise be considered experimental and recommended only in the context of a properly regulated clinical study. Understandably, most neurologists are unfamiliar with AHSCT procedures and the specific requirements for quality assurance and safety standards, as well as post-procedure precautions and follow-up. Consequently they may feel ill-equipped to advise patients. Here, we highlight important points for discussion in consultations with patients considering stem cell 'tourism' for MS.